Development of a duplex real-time RT-PCR assay for the detection and identification of two subgroups of human metapneumovirus in a single tube - Sugimoto, Satoko; Kawase, Miyuki; Suwa, Reiko; Kakizaki, Masatoshi; Kume, Yohei; Chishiki, Mina; Ono, Takashi; Okabe, Hisao; Norito, Sakurako; Hosoya, Mitsuaki; Hashimoto, Koichi; Shirato, Kazuya (Journal of virological methods, 2023)
Human metapneumovirus (hMPV) is a common cause of respiratory infections in children. Many genetic diagnostic assays have been developed, but most detect hMPV regardless of the subgroup. In this study, we developed a real-time RT-PCR assay that can detect and identify the two major subgroups of hMPV (A and B) in one tube. Primers and probes were designed based on the sequences of recent clinical isolates in Japan. The assay showed comparable analytical sensitivity to a previously reported real-time RT-PCR assay and specific reactions to hMPV subgroups. The assay also showed no cross-reactivity to clinical isolates of 19 species of other respiratory viruses. In a validation assay using post-diagnosed clinical specimens, 98% (167/170) positivity was confirmed for the duplex assay, and the three specimens not detected were of low copy number. The duplex assay also successfully distinguished the two major subgroups for all 12 clinical specimens, for which the subgroup had already been determined by genomic sequencing analysis. The duplex assay described here will contribute to the rapid and accurate identification and surveillance of hMPV infections. •The assay can detect hMPV genotype A and B simultaneously in single test.•Non-specific reactions were not detected in clinical specimens or unrelated virus.•The assay guarantees sufficient analytical sensitivity for current circulating clade.•Suitable for epidemiological surveillance for how hMPV subgroups spread.